Production of allitol from D‐psicose by a novel isolated strain of Klebsiella oxytoca G4A4. (28th April 2014) - Han, Wenjia; Zhu, Yueming; Men, Yan; Yang, Jiangang; Liu, Can; Sun, Yuanxia
<x xml:space="preserve">Abstract</x> A novel bacterium capable of producing allitol from D‐psicose was isolated from soil and identified as Klebsiella oxytoca G4A4. An efficient method for the transformation of D‐psicose to allitol was achieved through the resting cell reaction. Ribitol as an inducer is suitable for cell cultivation, and cells are most active in Tris–HCl buffer (pH 8.0) at 37 °C with a density of 40 (OD600 nm). After the reaction, the final conversion rates of the washed cells were approximately 87, 83, and 55% at D‐psicose concentrations of 0.25, 0.5, and 1%, respectively. The product from D‐psicose was purified and determined to be allitol by high‐performance liquid chromatography and nuclear magnetic resonance spectroscopy.